Fire Sales in Frozen Markets - Ebrahimy, Ehsan (IMF Working Papers; Working Paper ;, 2019)
It is challenging to explain the collapse in the price of subprime mortgage-backed securities (MBS) during the Financial Crisis of 2008, using the existing models of fire-sale. I present a model to demonstrate that fire-sales may happen even when there is a relatively sizable pool of natural buyers and in the absence of asymmetric information, due to a coordination failure among buyers: buyers' waiting to trade at a lower price tomorrow, can lead to a collapse in the price and trade volume today. In particular, I show that when trade is decentralized and participation is endogenous, a medium level of asset demand and liquidity needs that are ex-pected to increase over time create complementarity among buyers' decisions to wait. This complementarity makes competitive markets prone to coordination failures and fire-sales accompanied by a collapse in the trade volume. Fire-sales may also be inefficient. I also discuss various policy options to eliminate the risk of fire-sales in such a setup.